2016
DOI: 10.1016/j.matchar.2016.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and nanoindentation of the rostrum of Curculio longinasus Chittenden, 1927 (Coleoptera: Curculionidae)

Abstract: The rostrum is an extension of the cuticle of the head of weevils (Coleoptera: Curculionidae) and is often used to bore holes for oviposition (the process of laying eggs) into host plant tissue where larval development occurs. In members of the genus Curculio Linnaeus, 1758, the rostrum is long, slender, and strongly curved, but is nevertheless used to excavate straight bore-holes in the fruit of various host plants, through significant deformation of this structure. In this study, scanning electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
4
16
0
Order By: Relevance
“…Figure shows the nanoindentation properties of the mouthparts in “dry” and “fresh” conditions. The maximum load for indentation was 10 mN, the load rate was 0.33 mN/s, and holding time was 30 s. A value of 0.3 for Poisson's ratio was used according to the literatures [0.25 for sheep horn (Warburton, ); 0.3 for rostrum of insect (Singh et al, ); 0.3 for elytra (Dai & Yang, )]. The Young's modulus and hardness were observed to be constant with respect to depth (plateau region) between ∼500 and 1000 nm (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the nanoindentation properties of the mouthparts in “dry” and “fresh” conditions. The maximum load for indentation was 10 mN, the load rate was 0.33 mN/s, and holding time was 30 s. A value of 0.3 for Poisson's ratio was used according to the literatures [0.25 for sheep horn (Warburton, ); 0.3 for rostrum of insect (Singh et al, ); 0.3 for elytra (Dai & Yang, )]. The Young's modulus and hardness were observed to be constant with respect to depth (plateau region) between ∼500 and 1000 nm (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite its documented performance in many Curculio species, it remains unknown how the rostrum of female acorn weevils can withstand the repeated, often extreme bending incurred during the process of egg‐chamber excavation. Previous work in the species Curculio longinasus Chittenden, 1927 revealed modifications to the cuticle of the rostral apex—the region exposed to the strongest degree of bending—that might be linked to the flexibility of the rostrum . This modified composite structure has not been fully characterized—and has not been examined in any other species in this genus—nor has it been demonstrated that the modifications to the cuticle meaningfully alter the mechanical behavior of the snout in the context of bending.…”
mentioning
confidence: 99%
“…However, acorn weevils in the genus Curculio Linnaeus, 1758 (Curculionidae in the sense of ref. ) instead exhibit unusual distal flexibility in an elongate extension of the head called the rostrum (snout) . The rostrum is a hollow, strongly curved (over 90° in some species), cylindrical, exoskeletal extension of the otherwise nearly spherical head, which bears at its apex the terminal chewing mouthparts .…”
mentioning
confidence: 99%
See 2 more Smart Citations